Peningkatan pengetahuan dan keterampilan siswa-siswi dalam pemanfaatan daun sirsak (Annona Muricata L.) untuk pencegahan dan pengobatan berbagai penyakit - Noni Zakiah; Munira Munira; Vonna Aulianshah; Rasidah Rasidah; Farida Hanum (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: The use of traditional medicines is increasingly massive, it takes packaging and handling practical ways for the community. Soursop leaf is one of the herbs known to have many pharmacological properties for health. Capsules are an alternative form of packaging that is efficient for the community because in addition to ease of use, it can also mask the unpleasant taste and smell of simplicia.Objectives:  This aims to improve the skills of students in the use of soursop (Annona Muricata L.) leaves for the prevention and treatment of various diseases.Methods: This study was used a quasi-experimental design with a postest only approach. This activity was carried out by providing counseling (lecture method) and providing skills on how to package the soursop leaf simplicia powder into a capsule shell on 28 November 2018 at Suka Makmur High School, Aceh Besar. Direct data collection, and analysis using t-dependent tests.Results: The results of the study have shown an increase in the skills of students in the use of soursop (Annona muricata L.) leaves for the prevention and treatment of various diseases after counseling (p <0.05).Conclusion: Increasing the knowledge of students related to prevention and treatment can be done through counseling, namely counseling about the use of soursop leaves (Annona muricata L.)